Haematological and biochemical values of the Mexican axolotl (Ambystoma mexicanum) kept in captivity in the Lima, Peru - Anaya-Lavalle, Brayan Alfonso (2021)
The axolotl is a caudate amphibian used in numerous biomedical studies for its regenerative capacity. It is currently in the category of critical danger of extinction because of aquatic pollution, indiscriminate hunting and introduction of invasive species into its environment. The objective of the present study was to determine the ranges of haematological and biochemical parameters of captive axolotls in Lima, Perú, so that they can be used as reference values during the clinical evaluation in biomedical laboratories and veterinary clinics of unconventional species. The study was carried out in a private collection of axolotls in the district of San Juan de Miraflores, Lima. In total, 27 axolotls were used, which were chemically restricted to perform the blood collection, establishing reference ranges for 13 haematological and 10 biochemical parameters.